Complementary Sequential Circulating Tumor Cell (CTC) and Cell-Free Tumor DNA (ctDNA) Profiling Reveals Metastatic Heterogeneity and Genomic Changes in Lung Cancer and Breast Cancer - Kong, Say Li; Liu, Xingliang; Tan, Swee Jin; Tai, Joyce A.; Phua, Ler Yee; Poh, Huay Mei; Yeo, Trifanny; Chua, Yong Wei; Haw, Yu Xuan; Ling, Wen Huan; Ng, Raymond Chee Hui; Tan, Tira J.; et al. (Frontiers in Oncology, 2021)
Introduction: Circulating tumour cells (CTCs) and cell-free tumour DNA (ctDNA) are tumour components present in circulation. Due to the limited access to both CTC enrichment platforms and ctDNA sequencing in most laboratories, they are rarely analyzed together. Methods: Concurrent isolation of ctDNA and single CTCs were isolated from lung cancer and breast cancer patients using the combination of size-based and CD45-negative selection method via DropCell platform. We performed targeted amplicon sequencing to evaluate the genomic heterogeneity of CTCs and ctDNA in lung cancer and breast cancer patients. Results: Higher degrees of genomic heterogeneity were observed in CTCs as compared to ctDNA. Several shared alterations present in CTCs and ctDNA were undetected in the primary tumour, highlighting the intra-tumoural heterogeneity of tumour components that were shed into systemic circulation. Accordingly, CTCs and ctDNA displayed higher degree of concordance with the metastatic tumour than the primary tumour. The alterations detected in circulation correlated with worse survival outcome for both lung and breast cancer patients emphasizing the impact of the metastatic phenotype. Notably, evolving genetic signatures were detected in the CTCs and ctDNA samples during the course of treatment and disease progression. Conclusions: A standardized sample processing and data analysis workflow for concurrent analysis of CTCs and ctDNA successfully dissected the heterogeneity of metastatic tumour in circulation as well as the progressive genomic changes that may potentially guide the selection of appropriate therapy against evolving tumour clonality.